Perkembangan Relasi Negara dan Agama Paska Reformasi Konstitusi - Ferry Herlius; Donna Rumiris Sitorus (Universitas Airlangga, 2022)
AbstractSpeaking of the number of religions in Indonesia, juridically, since the past until now Indonesia has not designated one particular religion as a state religion nor does it make Indonesia a religious state. The position taken by the Indonesian state is in line with the theory and conception of a symbiotic state, it can be seen with the emergence of laws that meet the needs of all religions in Indonesia. This paper will discuss the relationship between religion and the state in historical currents, as well as the guarantee of religious freedom in positive law and international conventions. The method used in discussing this matter is a normative research method, with primary legal materials consisting of laws and regulations and secondary legal materials consisting of literature literature. The approach used is a statute approach and a conceptual approach. The results showed that religion and state in Indonesia have a dynamic pattern from the beginning of independence to the present. The relationship of religion and the state, has a symbiotic pattern of mutualism. The state needs religion as a source of morality for the administration of the state and the social system of society, religion needs the state to facilitate worship and certain religious needs of each religion. Keywords: Relation; State and Religioin; Amandement Constitution. AbstrakBicara banyaknya agama di Indonesia, secara yuridis, sejak dahulu hingga saat ini Indonesia tidak menetapkan satu agama tertentu menjadi agama negara dan juga tidak menjadikan Indonesia sebagai negara agama. Posisi yang diambil negara Indonesia sejalan dengan teori dan konsepsi negara simbiotik, hal itu terlihat dengan munculnya undang-undang yang memenuhi kebutuhan seluruh agama di Indonesia. Tulisan ini akan membahas mengenai relasi agama dan negara dalam arus sejarah, serta jaminan kebebasan beragama dalam hukum positif dan konvensi internasional. Metode yang digunakan dalam membahas hal tersebut adalah metode penelitian normatif, dengan bahan hukum primer yang terdiri dari peraturan perundang-undangan dan bahan hukum sekunder yang terdiri dari literatur kepustakaan. Pendekatan yang digunakan adalah pendekatan peraturan perundang-undangan dan pendekatan konseptual. Hasil penelitian menunjukkan bahwa agama dan negara di Indonesia memiliki pola yang dinamis sejak awal kemerdekaan hingga saat ini. Relasi agama dan negara, memiliki pola simbiosis mutualisme. Negara membutuhkan agama sebagai sumber moralitas bagi penyelenggaraan negara dan tata sosial kemasyrakatan, agama membutuhkan negara untuk memfasilitasi peribadatan dan kebutuhan keagaamaan tertentu dari tiap-tiap agama. Kata Kunci: Relasi; Negara dan Agama; Amandemen Konstitusi.